Unternehmensfuḧrung und Unternehmenserfolg - Volker Petersen (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2003)
– Management and Entrepreneurial SuccessStarting point of the analysis are theoretical considerations about multi-causal reasons of the management influence on the entrepreneurial success. In the further continuation an economic model illustrating the guidance idea of multi-causality is presented as well as a statistical evaluation method coordinated with it. Basis for the statistical illustration of the multi-causal context is an causal-analytic evaluation procedure. A priori formulated causal relations between not observable exogenous and endogenous variables are illustrated by a structural model. The structural model corresponds to the logical starting point of the regression analysis to provide documentary evidence of cause and effect relations. The latent variables of the regression-analytic part are measured by observed indicator variables.The measuring model itself is closely related to the logical starting point of the factor analysis. The causal-analytic evaluation procedure thus links the measuring models with cause and effect models.The formulation and examination of hypotheses are explained by case studies as a result of limited data. It refers only to the context between the market-focused management and the entrepreneurial success on the one hand as well as production and technology-oriented management and the entrepreneurial success on the other. Further unresolved tasks like further dimensions of the management - like employee orientation or financial orientation - have to be analysed more in detail. This task also gains significance because changes in the relative relevance of the identified management dimensions are to be expected.
Keywords: 330; Unternehmenserfolg; Management; Kausalanalyse